Virtual versus face-to-face clinical simulation in relation to student knowledge, anxiety, and self-confidence in maternal-newborn nursing: A randomized controlled trial. (October 2016) - Cobbett, Shelley; Snelgrove-Clarke, Erna
Abstract: Background: Clinical simulations can provide students with realistic clinical learning environments to increase their knowledge, self-confidence, and decrease their anxiety prior to entering clinical practice settings. Objective: To compare the effectiveness of two maternal newborn clinical simulation scenarios; virtual clinical simulation and face-to-face high fidelity manikin simulation. Design: Randomized pretest-posttest design. Setting: A public research university in Canada. Participants: Fifty-six third year Bachelor of Science in Nursing students. Methods: Participants were randomized to either face-to-face or virtual clinical simulation and then to dyads for completion of two clinical simulations. Measures included: (1) Nursing Anxiety and Self-Confidence with Clinical Decision Making Scale (NASC-CDM) (White, 2011), (2) knowledge pretest and post-test related to preeclampsia and group B strep, and (3) Simulation Completion Questionnaire. Before and after each simulation students completed a knowledge test and the NASC-CDM and the Simulation Completion Questionnaire at study completion. Results: There were no statistically significant differences in student knowledge and self-confidence between face-to-face and virtual clinical simulations. Anxiety scores were higher for students in the virtual clinical simulation than for those in the face-to-face simulation. Students' self-reported preference was face-to-face citing the similarities to practicing in a 'real' situation and the immediate debrief. Students not liking the virtual clinical simulation most often cited technological issues as their rationale. Conclusions: Given the equivalency of knowledge and self-confidence when undergraduate nursing students participate in either maternal newborn clinical scenarios of face-to-face or virtual clinical simulation identified in this trial, it is important to take into the consideration costs and benefits/risks of simulation implementation. Highlights: Virtual clinical simulations may be a useful method to bridge the theory to practice gap and increase student readiness for clinical practice. Recent evidence demonstrates positive benefits of high-fidelity simulation with up to 50% of clinical practice replaced with simulation. No significant differences were found in student knowledge or self-confidence levels between a face-to-face high fidelity and a virtual clinical simulation Students' self-reported anxiety levels were higher when participating in virtual clinical simulations. Students' preferred the face-to-face simulation verses the virtual clinical simulation, mainly related to technological issues.